1993
DOI: 10.1080/01919519308552483
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization Of Textile Dye Solutions

Abstract: Results are presented on the use of ozone to decolorize textile dye solutions. The results describe the rates of reaction and the stoichiometry for the use of ozone to decolorize a simulated wastewater containing a bisazo acid dye (Acid Red 158). These rates of reaction are not sensitive to pH and are only mildly affected by temperature. The effects of a combination of an uncolored organic compound on the rates of reaction were investigated because if ozone reacts preferentially with uncolored compounds, its u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 2 publications
2
21
0
Order By: Relevance
“…They include physicalchemical flocculation, electroflotation, membranefiltration, electrokinetic coagulation, ion-exchange, irradiation, precipitation and other treatment using activated carbon. 5 Over the past few years, alternative methods [6][7][8][9][10] for dye treatment have been investigated, including chemical oxidation with reagents such as: ozone, hydrogen peroxide, ozone/UV, hydrogen peroxide/UV and Fenton's reagent [hydrogen peroxide + Fe (II)]. The application of electrochemical oxidation with or without UV light as method for dye degradation have also been investigated, [11][12][13][14][15] but no mechanisms of the reduction were discussed.…”
Section: Introductionmentioning
confidence: 99%
“…They include physicalchemical flocculation, electroflotation, membranefiltration, electrokinetic coagulation, ion-exchange, irradiation, precipitation and other treatment using activated carbon. 5 Over the past few years, alternative methods [6][7][8][9][10] for dye treatment have been investigated, including chemical oxidation with reagents such as: ozone, hydrogen peroxide, ozone/UV, hydrogen peroxide/UV and Fenton's reagent [hydrogen peroxide + Fe (II)]. The application of electrochemical oxidation with or without UV light as method for dye degradation have also been investigated, [11][12][13][14][15] but no mechanisms of the reduction were discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Ozone specifically attacks the conjugated chains that impart color to the dye molecule (Horvath et al, 1985). It has been demonstrated that they have the ability to destroy dyestuffs (Saunders et al, 1983;Carrière et al, 1993). Ozonation of dyestuffs does not generate more biologically toxic chemicals (Gähr et al, 1994) and indeed, biodegradation appears by ozonation of wastes (Sevimli, 2002;Perkowski et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Dye solutions were prepared with de-ionised water, and after adjusting the pH to the required value with diluted H 2 SO 4 . After ozonation the treated solutions were transferred to glass bottles, the solution decanted after 2 h, and their absorbance measured.…”
Section: Fenton-like Oxidation Alone and Combined With Ozonationmentioning
confidence: 99%